A Survey On Channel Estimation In Mimo-Ofdm Systems (International Journal of Engineering and Computer Science, 2017)
In Communication Systems, MIMO (Multiple Input Multiple Output) Channel have been introduced to achieve high data speed and better bit rate. The system becomes more efficient when OFDM (Orthogonal Frequency Division Multiplexing) is combined with MIMO to obtain high transmission rates, good quality of service and minimize the probability of error. Channel estimation is of great importance in MIMO-OFDM system. Channel estimation is used to estimate the transmitted signal using the corresponding receiver signal. Channel capacity of MIMO-OFDM system is also increased by channel estimation. A main challenge in MIMO-OFDM system is retrieval of the channel state information accurately. Channel state information is retrieved with the help of channel estimation i.e. all the channels between the transmit antenna are accurately known. In this paper we describe the basic introduction of MIMO-OFDM system and survey the different channel estimation techniques used in MIMO-OFDM system considering the various system parameters.